Encountering Chinese networks : Western, Japanese, and Chinese corporations in China, 1880-1937 - Cochran, Sherman, 1940- (University of California Press, 2000)
The text studies how various Western, Japanese, and Chinese businesses struggled with the persistent dilemma in China of how to retain control over corporate hierachies while adapting to dramatic changes in Chinese society, politics and foreign affairs from 1880-1937.